2011
DOI: 10.1007/s00726-011-1028-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transgenic mice with overexpression of spermidine synthase

Abstract: A composite cytomegalovirus-immediate early gene enhancer/chicken β-actin promoter (CAG) was utilized to generate transgenic mice that overexpress human spermidine synthase (SpdS) in order to determine the impact of elevated spermidine synthase activity on murine development and physiology. CAG-SpdS mice were viable and fertile and tissue SpdS activity was increased up to 9-fold. This increased SpdS activity did not result in a dramatic elevation of spermidine or spermine levels but did lead to a 1.5 to 2-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This provides a great deal of discrimination in favor of the smaller substrate (more than 100‐fold). However spermidine synthase is present in much larger amounts than SpmSyn [in mice approximately 25 times in heart; 400 times in liver, and 40 times in brain ] Thus, even 0.5% activity would provide a considerable capacity to produce spermine, particularly, since levels of dcAdoMet, the other substrate for the reaction, are increased.…”
Section: Comparison Of Alterations In Polyamine Content and In Phenotmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a great deal of discrimination in favor of the smaller substrate (more than 100‐fold). However spermidine synthase is present in much larger amounts than SpmSyn [in mice approximately 25 times in heart; 400 times in liver, and 40 times in brain ] Thus, even 0.5% activity would provide a considerable capacity to produce spermine, particularly, since levels of dcAdoMet, the other substrate for the reaction, are increased.…”
Section: Comparison Of Alterations In Polyamine Content and In Phenotmentioning
confidence: 99%
“…However, several altered residues could limit this space even more either directly or by slightly changing the position of Trp28. Transgenic mice in which human spermidine synthase is expressed from a ubiquitous promoter are available and cells derived from crosses of these mice with the Gy mice could be used to test this hypothesis.…”
Section: Comparison Of Alterations In Polyamine Content and In Phenotmentioning
confidence: 99%
“…In summary, our ternary hybrid promoter/enhancer design containing a casein or a BLG promoter, a CMV enhancer, and a binary chicken β‐globin insulator can be considered a first step toward creating and validating an improved mammary gland‐specific vector, which ensures high‐level expression of the transgene, independent of the integration site. This newly developed vector may be used as a robust promoter for gene‐specific expression, particularly to direct mammary‐specific expression of transgenes, similar to the CAG promoter that consists of the CMV enhancer, the chicken β‐actin promoter, and an intron (Xu et al, 2001; Ito et al, 2006; Shi et al, 2012). Further confirmation of the efficacy of this unique hybrid promoter/enhancer vector is currently underway in domestic animals, such as rabbit, goat, pig, and cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The speculated variation in these results can be associated to the breed specific difference complex. Mostly abundant polyamines in the animal cells include spermidine, which is produced through the conversion of putrescine by spermidine synthase (SRM) in the polyamine biosynthesis pathway to promote cell growth (Shi et al 2012) . The results showed that the SRM gene was highly expressed in PE, with minimal expression in MWF, in which there was no remarkable expression difference between the SWF and SYF (p > 0.05) but significantly lower than LWF (p  0.05).…”
Section: Resultsmentioning
confidence: 99%